The stem xylem of Patagonian shrubs operates far from the point of catastrophic dysfunction and is additionally protected from drought- induced embolism by leaves and roots - Bucci, Sandra Janet (2013)
Hydraulic architecture was studied in shrub species differing in rooting depth in a cold desert in Southern Argentina. All species exhibited strong hydraulic segmentation between leaves, stems and roots with leaves being the most vulnerable part of the hydraulic pathway. Two types of safety margins describing the degree of conservation of the hydraulic integrity were used: the difference between minimum stem or leaf water potential (⍦) and the ⍦ at which stem or leaf hydraulic function was reduced by 50% ⍦ - ⍦50), and the difference between leaf and stem ⍦50. Leaf ⍦50 -⍦ stem ⍦50 increased with decreasing rooting depth. Large diurnal decreases in rootspecific hydraulic conductivity suggested high root vulnerability to embolism across all species. Although stem ⍦50 became more negative with decreasing species-specific Ysoil and minimum stem⍦, leaf ⍦50 was independent of ⍦ and minimum leaf ⍦. Species with embolism-resistant stems also had higher maximum stem hydraulic conductivity. Safety margins for stems were >2.1 MPa, whereas those for leaves were negative or only slightly positive. Leaves acted as safety valves to protect the integrity of the upstream hydraulic pathway, whereas embolism in lateral roots may help to decouple portions of the plant from the impact of drier soil layers.